Análisis de vulnerabilidades e incidencias en el software contable de la empresa Maromsa Cia. Ltda. de la ciudad de Babahoyo - Espín Vásquez, Deysi Evelyn (2019)
This work is entitled “Analysis of vulnerabilities and incidents in the accounting software of the company MAROMSA Cía. Ltda. Of the city of Babahoyo ”, the information has been collected through observation, the objective of this case study is to identify the vulnerabilities of the accounting system of the company, the analysis was carried out because the company wishes to have financial health and control of the income and expenses of the company, you must have all the security measures, have protocols that ensure that purpose, you will proceed to use different research techniques such as the interview and the survey that consists in carefully observing the case, taking information and record it for later analysis